Can digital technology use enhance livelihood capital for mining farmers? A moderated mediation model - He, Xuesong; Wei, Jianzhi; Wu, Yawei (Frontiers in Sustainable Food Systems, 2025)
In the context of digital rural construction, based on the theory of livelihood capital, this paper uses 312 survey data collected in mining areas of Shanxi Province in 2023 as a sample, and uses hierarchical regression and bootstrap methods to empirically test the impact path of digital technology use on farmers’ livelihood capital. Among them, the hierarchical regression method tests the main effect and mediation effect, and the bootstrap method tests the robustness of the mediation effect and the moderated mediation effect. The results show that the use of digital technology significantly improves the level of farmers’ livelihood capital. Collective action plays a mediating role in the relationship of this impact path. Risk perception positively regulates the relationship between digital technology use and collective action, indirectly affecting livelihood capital through collective action. Heterogeneity analysis shows that the improvement effect is more significant among male and elderly farmers. Further analysis shows that the frequency of online shopping, leisure and entertainment, and business activities all positively impact livelihood capital, among which online business activities have the most significant impact. The increase in household mobile phone service fees and the popularization of online shopping help stimulate the potential for capital appreciation, but the marginal effect is decreasing. Based on this, policy recommendations are put forward, such as strengthening digital technology training for farmers and supporting the combination of production and operation.